The impact of market orientation on the performance of MSMEs operating in technology parks: The role of market dynamism - Anna Wójcik-Karpacz; Jarosław Karpacz; Joanna Rudawska (Journal of Entrepreneurship, Management and Innovation, 2021)
Purpose: The purpose of this article is to identify the role of market dynamism in the relationship between market orientation and the performance of micro, small, and medium enterprises (MSMEs) operating in technology parks (TPs) in Poland. Methodology: The two methods used for performing the quantitative empirical research are CAWI and PAPI. The research sample included MSMEs operating in technology parks in Poland. The article is the answer to the needs for systematic research of models between market orientation and firm performance. Findings: The research findings provide an insight into the level of market orientation and performance of the analyzed MSMEs operating in technology parks in Poland. It was found that MSMEs in the research sample were not a homogeneous group in this respect. It has been proven that market orientation is a significant stimulant of firm performance, while market dynamism has not been classified as a moderator of the market orientation–firm performance relationship. Implications for theory and practice: This study contributes to strategic management by identifying the key role of market orientation for enterprises wishing to benefit from this type of strategic orientation. The important role of the predictor – market orientation in shaping the results of micro, small and medium-sized enterprises operating at TPs in Poland has been proven. In practice, this means that increasing the level of market orientation is conducive to increasing positively assessed financial performance. Originality and value: Our research carried out at MSMEs operating in technology parks in Poland enriches and supplements knowledge about market orientation as a phenomenon of universal character because it also applies to smaller sized business organizations